"Mitzvah" mistranslated: Reimagining Aquinas' threefold division of "Old Law" - Latham, Elizabeth ca. 20./21. Jh. (Scottish journal of theology, 2025)
Thomas Aquinas argues that "Old Law", comprised of the precepts found in the Hebrew Bible, should be divided into three types: moral, ceremonial and judicial. His system is meant to be instructive for Christian ethics, distinguishing between eternally, universally binding precepts relevant to Christians and other irrelevant or even forbidden ones. But Aquinas derives this threefold division from a mistranslated Vulgate passage from Deuteronomy where a singular noun, mitzvah, is translated as a plural noun: praecepta. Based on the original Hebrew, the verse actually supports a twofold division, not a threefold one. Aquinas' system also runs into issues when it comes to sorting the precepts. To fix the sorting, retain the instructive benefit, and shed the biblical tension, we ought to keep Aquinas' understanding of "moral law", but discard the judicial and ceremonial categories in favour of one "cultural law" category, in line with the popular Jewish philosophical division between chukim and mishpatim.